Review of Ukrainian health care reformation on principles of family medicine - Tkachenko, Victoria I. (Family Medicine & Primary Care Review, 2017)
This article presents the steps of family medicine implementation in Ukraine, the results and problems of reorganization of the health system, educational and economic problems and the role of the Institute of Family Medicine at the Shupyk National Medical Academy of Postgraduate Education in all processes. The new structure of primary care includes centers with administrative facilities, several ambulatory primary care clinics and emergency care departments. The main problem is to provide a substantial quantity of general practitioners (GPs) to cover affordable primary care for the Ukrainian population (42 million). The target is approximately 28,000 working GPs for the short period of 2011–2020, where in 2016, there were approximately 14,000 GPs. Other problems include the insufficient financing and equipment of primary care centers, low number of computers, paper medical records and low salary. The situation has been worsened since 2014 when the antiterroristic operation was started and funding of primary care was cut. Further steps of reformation according to the plan of the Ministry of Health of Ukraine are: reformation of the financing system, organization of hospital areas, autonomization of health establishments, creation of centers of public health, wide implementation of licensing and health insurance, state reimbursement of medications for patients, implementation of syndrome classification ICPC-2, improvement of national clinical guidelines and implementation of digital medical records. The reformation of the health system of Ukraine upon the principles of family medicine for 30 years, more active in the last 5 years, showed some positive results, but at the same time determined the existence of quality problems in medical education and financing of primary care.